Digital systems design using Verilog - Roth, Charles H.; John, Lizy Kurian; Lee, Byeong Kil (Cengage Learning, 2016)
This book combines coverage of logic design principles, Verilog as a hardware design language, and FPGA implementation. It offers Verilog constructs along with hardware, encouraging you to think in terms of desired hardware while writing synthesizable Verilog.